Astrological Sayings of Geomancy in the Praises of Sacred Places and Monasteries - Magsarjav, Gankhuyag (Tibetan Studies, 2024)
In this article, I intend to study one of the features of the praise of sacred places and monasteries composed in the Tibetan language by Mongolian scholars. In Mongolian tradition, it is customary to assess the suitability of areas for graveyards, distinguishing between those for nobility and ordinary individuals, as well as for pasture land to support livestock. This assessment is integral to processes such as relocating, engaging in agriculture, and constructing cities, temples, and stupas. As we examine the praises of sacred places and monasteries, it is essential to understand the symbolic expressions contained within them. This involves analyzing the methodologies employed and summarizing the findings from various sources. This article provides a specific example demonstrating how the features of the land are eloquently praised, progressing from general to specific, in the Tibetan-language praises of sacred places and monasteries composed by Mongolian scholars. Understanding how traditional knowledge and the science of geomancy are described in these praises is an important area of study. Identifying the most significant features among the main attributes and making this knowledge accessible to Mongolians in urban areas is crucial. Geomantic knowledge is a vital skill that cannot be overlooked, even though it is becoming less recognized today. Орон хийдийн магтаал дахь зурхайн ухааны газрын шинжийн өгүүлэмжүүд Хураангуй: Энэхүү өгүүллээр монголчуудын төвөд хэлээр зохиосон орон, хийдийн магтаалын хөгжилд оруулсан өвөрмөц нэгэн өгүүлэмж болох газрын шинжийг хэрхэн тусгасан тухай өгүүлэхийг зорилоо. Монголчууд эртнээс уламжилж ирсэн уламжлалт мэдлэг ухааны нэг газар шинжих уламжлалт ойлголт бөгөөд сав ертөнц болох газар орноо ихэс дээдс, нас нөгчсөн нэгнээ өлгий болох газар, малын бэлчээр, бууц бууриа сонгох, газар тариалан эрхлэх, хот балгад босгох, сүм дуган, суварга шүтээн барих газар орноо шинжиж ирсэн байдаг. Орон, хийд магтаалын шүлгүүдэд тухай хийд, орныг барихдаа бэлгэдлийн үүднээс мөн уламжлалт ахуй ёсны талаас эх бичиг сурвалжид тулгуурлан задлан шинжлэх нэгтгэн дүгнэх болон үзэгдлийн /феноминологи/ аргаар хэрхэн авч үзсэн талаар өгүүлэх юм. Энэ өгүүлэлд монголчуудын төвөд хэлээр зохиосон орон, магтаалд газрын шинжийг ерөнхийгөөс тодорхой руу хэрхэн уран яруугаар шүлэглэн магтаж байгааг тодорхой жишээн дээр авч үзүүллээ. Орон, хийдийн магтаалд газар шинжих уламжлалт мэдлэг, ухааныг уран яруугаар хэрхэн өгүүлсэн байна, гол шинжид ямар шинжийг илүүтэй чухалчилж байгааг тодруулж өнөө цагт хот суурин газрын монголчуудад таниулж мэдүүлэх нь чухал болжээ хэмээн үзэж байна. Газар шинжих мэдлэг ухаан нь өнөө цагт мартагдаж байгаа ч мөн орхиж болохгүй мэдлэг, ухааны нэг юм. Түлхүүр үг: Газар шинжих, төвөд хэлт уран зохиол, Бурхны шашин